Omega 3 polyunsaturated fatty acids and the treatment of depression. Issue 1 (2nd January 2017) - Deacon, Gelinda; Kettle, Christine; Hayes, David; Dennis, Christina; Tucci, Joseph
ABSTRACT: Depression is a common, recurrent, and debilitating illness that has become more prevalent over the past 100 years. This report reviews the etiology and pathophysiology of depression, and explores the role of omega 3 polyunsaturated fatty acids (n-3 PUFA) as a possible treatment. In seeking to understand depression, genetic factors and environmental influences have been extensively investigated. Research has led to several hypotheses for the pathophysiological basis of depression but a definitive pathogenic mechanism, or group thereof, has hitherto remained equivocal. To date, treatment has been based on the monoamine hypothesis and hence, selective serotonin reuptake inhibitors have been the most widely used class of medication. In the last decade, there has been considerable interest in n-3 PUFAs and their role in depression. These fatty acids are critical for development and function of the central nervous system. Increasing evidence from epidemiological, laboratory, and randomized placebo-controlled trials suggests deficiency of dietary n-3 PUFAs may contribute to development of mood disorders, and supplementation with n-3 PUFAs may provide a new treatment option. Conclusions based on systematic reviews and meta-analyses of published trials to date vary. Research into the effects of n-3 PUFAs on depressed mood is limited. Furthermore, results from such have led to conflicting conclusions regarding the efficacy of n-3 PUFAs in affecting reduction in symptoms of depression. PUFAs are generally well tolerated by adults and children although mild gastrointestinal effects are reported. There is mounting evidence to suggest that n-3 PUFAs play a role in depression and deserve greater research efforts.